Relating behaviours and therapeutic actions during AVATAR therapy dialogue: An observational study. (5th May 2021) - O'Brien, Conan; Rus‐Calafell, Mar; Craig, Tom KJ; Garety, Philippa; Ward, Thomas; Lister, Rachel; Fornells‐Ambrojo, Miriam
Abstract : Objectives: AVATAR therapy is a novel relational approach to working with distressing voices by engaging individuals in direct dialogue with a digital representation of their persecutory voice (the avatar). Critical to this approach is the avatar transition from abusive to conciliatory during the course of therapy. To date, no observational study has examined the moment‐to‐moment dialogical exchanges of this innovative therapy. We aim to (1) map relating behaviours between participants and their created avatars and (2) examine therapeutic actions delivered within AVATAR dialogue. Method: Twenty‐five of the fifty‐three AVATAR therapy completers were randomly selected from a randomized controlled trial (Craig et al. The Lancet Psychiatry, 5, 2018 and 31). Seventy‐five audio recordings of active dialogue from sessions 1 and 4 and the last session were transcribed and analysed using a newly developed coding frame. Inter‐rater reliability was good to excellent. Results: Fine‐grained analysis of 4, 642 observations revealed nuanced communication around relational power and therapeutic activity. Early assertiveness work, reinforced by the therapist, focussed on increasing power and distancing. Participants' submissive behaviours reduced during therapy, but the shift was gradual. Once the transition to a more conciliatory tone took place, the dialogue primarily involved direct communication between participant and avatar, focussing on sense of self and developmental and relational understanding of voices. Conclusions: AVATAR therapy supports voice‐hearers in becoming more assertive towards a digital representation of their abusive voice. Direct dialogue with carefully characterized avatars aims to build the voice‐hearers' positive sense of self, supporting the person to make sense of their experiences. Practitioner points: AVATAR therapy enables voice‐hearers to engage in face‐to‐face dialogue with a digital representation ('avatar') of their persecutory voice. Fine‐grained analyses showed how relating behaviours and therapeutic actions evolve during active AVATAR therapy dialogue. Carefully characterized avatars and direct therapist input help voice‐hearers become more assertive over the avatar, enhance positive sense of self, and support individuals to make sense of their experiences.